SENTIMEN KEAGAMAAN SEBAGAI PONDASI BISNIS STUDI PADA MINIMARKET 212 MART MUTIARA GADING TIMUR MUSTIKAJAYA - KOTA BEKASI - Jaenudin Jaenudin (Institut Bisnis Muhammadiyah Bekasi, 2022)
The current economic systems ruled mostly are socialist and capitalist. Islamic system or economy sharia presented Muslim power to run their own based on their belief. The unique point of 212 retail mart establishment is based on the emotional and religious feeling of Muslim power in the event of 212. This research focused on how this business was managed and its results after more than five years. This study aims to escalate whether religious sentiment feelings can run the business smoothly or it is only euphoria that still needs many areas of improvement in managing this retail mart.